2014
DOI: 10.1186/2193-1801-3-273
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of conservation and utilization of pineapple genetic resources in Benin

Abstract: Valuation of farmer knowledge has been seen as a route to promote sustainable use of plant genetic resources. In pineapple production systems in Benin, inadequate knowledge of cultivation practices can lead to a number of inconveniences including abandon of some varieties and cultivars. To understand how farmer’s knowledge and cultivation practices impact the sustainable utilization of pineapple genetic resources, we surveyed 177 pineapple farmers in southern Benin. We assessed farmers’ knowledge and analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…This observation substantiated findings in similar studies showing the abandonment of varieties farmers found less desirable [11, 37, 52, 53]. The abandonment of less preferred varieties could be explained by the fact that farmers’ preferences lie in their desire to adapt to their biophysical environment, cropping systems [12, 53] and meet consumers preferences (eg: preference to white seed color) [37, 52, 54]. Despite some undesirable traits mentioned by farmers as reason for their abandonment, these varieties may have some traits that can be exploited in breeding programs for further adaptation.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This observation substantiated findings in similar studies showing the abandonment of varieties farmers found less desirable [11, 37, 52, 53]. The abandonment of less preferred varieties could be explained by the fact that farmers’ preferences lie in their desire to adapt to their biophysical environment, cropping systems [12, 53] and meet consumers preferences (eg: preference to white seed color) [37, 52, 54]. Despite some undesirable traits mentioned by farmers as reason for their abandonment, these varieties may have some traits that can be exploited in breeding programs for further adaptation.…”
Section: Discussionsupporting
confidence: 84%
“…Threats on traditional knowledge related to diversity use and conservation are increasing [10]. Changes occurring in agricultural systems resulting from globalization, urbanization, agro-industrialization and intensification of agricultural systems have led to over reliance on production of few major crops and few elite cultivars [4, 10–12]. Consequently, there is a decline in production and diversity of so-called minor crops, important for food security in marginal areas, and the traditional knowledge associated to their conservation [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively low proportion of female involved in pigeonpea production as compared to other crops may be explained by its long life cycle, and then, its cultivation requires access to land on long duration. Such condition is difficult to fulfill by female who, in Benin, are rarely landowner [20]. Popularization of early or extra-early-maturing cultivars may make the cultivation of pigeonpea more attractive to women.…”
Section: Pigeonpea Production Practices and Gender Rolementioning
confidence: 99%
“…This knowledge gap may limit the efficiency of interventions seeking to promote pigeonpea production in the country. Identification of farmers' preferences traits is useful for breeders in developing preferred varieties and for extension agents in appropriate choice of varieties to be popularized [20][21][22]. In addition, knowledge on production systems and the rationale driving farmers' practices are key requirements for guiding successful variety introduction.…”
Section: Introductionmentioning
confidence: 99%